Høyere musikkutdanning - Varkøy, Øivind; Stabell, Ellen M.; Utne-Reitan, Bjørnar; Christensen, Solveig; Eriksson, Karin; Gies, Stefan; Johansen, Geir; Jørgensen, Harald; Pedersen, Gjertrud; Ruud, Even; Schaathun, Asbjørn; Siems, Christoph; et al. (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2024)
This anthology offers historical perspectives on higher music education, with a particular focus on the origins and development of the Norwegian Academy of Music. It is published in connection with the Academy's 50th anniversary in 2023.